Graduating Out of Poverty Across Generations: Unpacking Children's Well‐being Trajectories in Burundi. (9th June 2019) - Roelen, Keetie; Leon‐Himmelstine, Carmen
Abstract : Graduation model interventions represent a new wave of anti‐poverty programming that seeks to offer a sustainable pathway out of poverty. An expanding evidence base points towards positive economic outcomes at household level but little is known about impacts on child well‐being. This paper investigates children's well‐being in Burundi during and after participation in a graduation model programme using a longitudinal mixed‐methods approach. The programme is found to improve child well‐being, particularly in relation to housing, food security and education. Covariate shocks undermine sustainability of effects but greater knowledge, experience and prioritisation of children's needs contribute to harnessing improved outcomes.